2022
DOI: 10.3390/antiox12010025
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Nitrate Supplementation Enhances Performance and Speeds Muscle Deoxyhaemoglobin Kinetics during an End-Sprint after Prolonged Moderate-Intensity Exercise

Abstract: Short-term dietary nitrate (NO3−) supplementation has the potential to enhance performance during submaximal endurance, and short-duration, maximal-intensity exercise. However, it has yet to be determined whether NO3− supplementation before and during submaximal endurance exercise can improve performance during a short-duration, maximal-intensity end-sprint. In a randomised, double-blind, crossover study, 9 recreationally active men ingested NO3−-rich (BR: 8 mmol NO3−/day) and NO3−-depleted (PL: 0.75 mmol NO3−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…as a means of enhancing muscle performance or recovery). The following situations were compared with some control scenarios to evaluate the muscle oxygenation responses and the potential benefits of the tested product or intervention: the use of a tracksuit jacket with heating elements [ 162 ], nonivamide-nicoboxil cream [ 180 ], sports compression garment ( n = 3 for lower limb: tights, calf sleeve, socks; n = 1 for upper limb, forearm) [ 18 , 19 , 31 , 107 ], core and skin cooling [ 136 ], undergoing thigh cooling by a water-circulating pad [ 85 ] and oral supplementation with dietary inorganic nitrate-rich and placebo beetroot juice [ 32 , 33 , 40 , 43 , 63 , 75 , 76 , 131 , 146 , 158 , 183 , 190 , 201 ], supplementation with pomegranate extract and co-supplementation with N -acetylcysteine [ 39 ], protein powder [ 134 ], pre-exercise ingestion of a drink with higher dissolved O 2 [ 135 ], anthocyanin-rich New Zealand blackcurrant supplementation [ 27 ], 1 h after a single dose of mango leaf extract rich in mangiferin and lecithin, or mango leaf extract rich in mangiferin and quercetin, phospholipids addition [ 53 55 ], red spinach extract [ 121 ], citrulline drink/citrulline malate [ 190 , 196 ], l -arginine [ 141 , 143 ], Montmorency cherry polyphenols [ 67 ], eicosapentaenoic acid and docosahexaenoic acid (fish oil) [ 198 ], caffeine intake [ 189 ] and dark chocolate [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…as a means of enhancing muscle performance or recovery). The following situations were compared with some control scenarios to evaluate the muscle oxygenation responses and the potential benefits of the tested product or intervention: the use of a tracksuit jacket with heating elements [ 162 ], nonivamide-nicoboxil cream [ 180 ], sports compression garment ( n = 3 for lower limb: tights, calf sleeve, socks; n = 1 for upper limb, forearm) [ 18 , 19 , 31 , 107 ], core and skin cooling [ 136 ], undergoing thigh cooling by a water-circulating pad [ 85 ] and oral supplementation with dietary inorganic nitrate-rich and placebo beetroot juice [ 32 , 33 , 40 , 43 , 63 , 75 , 76 , 131 , 146 , 158 , 183 , 190 , 201 ], supplementation with pomegranate extract and co-supplementation with N -acetylcysteine [ 39 ], protein powder [ 134 ], pre-exercise ingestion of a drink with higher dissolved O 2 [ 135 ], anthocyanin-rich New Zealand blackcurrant supplementation [ 27 ], 1 h after a single dose of mango leaf extract rich in mangiferin and lecithin, or mango leaf extract rich in mangiferin and quercetin, phospholipids addition [ 53 55 ], red spinach extract [ 121 ], citrulline drink/citrulline malate [ 190 , 196 ], l -arginine [ 141 , 143 ], Montmorency cherry polyphenols [ 67 ], eicosapentaenoic acid and docosahexaenoic acid (fish oil) [ 198 ], caffeine intake [ 189 ] and dark chocolate [ 81 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies focused on analyzing the effects of creatine as a supplement [ 21 , 22 ], while six others focused on sodium bicarbonate [ 23 , 24 , 25 , 26 , 27 , 28 ]. Beta-alanine supplementation was evaluated in three studies [ 29 , 30 , 31 ], and eight studies assessed nitrates [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. Notably, none of the trials specifically addressed glycerol supplementation.…”
Section: Resultsmentioning
confidence: 99%
“…Eight studies investigating nitrate supplementation during cycling were examined [ 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 ]. In one study, a dose of 6.4 mmol of nitrates was administered [ 34 ], while doses of 8 mmol of nitrates were used in two studies [ 36 , 38 ], a dose of 9.9 mmol of nitrates in one study [ 35 ], doses ranging from 12.4 to 13 mmol of nitrates in two studies [ 33 , 39 ], and a dose of 18.5 mmol of nitrates in another study [ 37 ]. One study mentioned only the consumption of 340 mg of nitrates without specifying the equivalence in mmol [ 32 ].…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, NO 3 − supplements intake could potentially offer positive effects in high-intensity efforts where the ability to deliver and maintain high peak power is determinant, such as rowing (Bell et al 1989 ). Wylie et al ( 2013b ) found, in recreational team-sport players, improvements in 6 s sprints after supplementing 8.4 mmol NO 3 − for 8 days, but no other benefits were reported in sprints lasting between 30 and 60 s. However, using similar supplementation (8 mmol NO 3 − for 7 days), benefits in 60 s sprint have been found in active men (Rowland et al 2023 ). Although other benefits have been reported in efforts lasting 30–60 s such as after a Wingate test (i.e., 45 s), these studies used acute intake of NO 3 − (Dominguez et al 2017b ; Jodra et al 2020 ).…”
Section: Discussionmentioning
confidence: 99%